Quantification of the nutrition of grazing Arsi cattle through prediction of diet composition, feed intake and digestibility using plant wax markers - Hassen, Abubeker (University of Pretoria, 2022)
Thesis (PhD (Animal Science))--University of Pretoria, 2022.